Wide Bandgap Semiconductor Based Micro/Nano Devices - Seo, Jung-Hun (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
While group IV or III-V based device technologies have reached their technical limitations (e.g., limited detection wavelength range or low power handling capability), wide bandgap (WBG) semiconductors which have band-gaps greater than 3 eV have gained significant attention in recent years as a key semiconductor material in high-performance optoelectronic and electronic devices. These WBG semiconductors have two definitive advantages for optoelectronic and electronic applications due to their large bandgap energy. WBG energy is suitable to absorb or emit ultraviolet (UV) light in optoelectronic devices. It also provides a higher electric breakdown field, which allows electronic devices to possess higher breakdown voltages. This Special Issue seeks research papers, short communications, and review articles that focus on novel synthesis, processing, designs, fabrication, and modeling of various WBG semiconductor power electronics and optoelectronic devices.